DENOTING THE CHARACTERS OF ORWELL’S ANIMAL FARM THROUGH SEMIOTICS - Lynda Susana Widya Ayu Fatmawaty (University of Muhammadiyah Purwokerto, 2011)
Orwell’s animal farm is called so as political fairy tale. This novel tried to elucidate the language abuse on how the ruling class controls the lower class. They impose an ideology to the lower class that they live better under the spirit of animalism. However, the intrigue and strategy are always used to linger the tyranny of the autocrat. The entire condition is well-designed so that the lower class believes everything. Therefore, none of them dares to question everything seems anomalous. The characters in Animal farm are twisted resemble to the qualities of human characters. In a certain way, they symbolize the characters of politicians, aristocrats, or even government officers. Therefore, this novel teaches the reader about hidden agenda of political systems instead of its function to give pleasure. The story goes under the aim of criticizing the universe about the intrigue in accomplishing ambitions and sustaining the profession. However, this paper focuses on denoting the characters through semiotics to reveal better understanding about this novel.